The Influence of Social Media Advertising on Purchase Intention Through Utilitarian and Hedonic Shopping Motivation: A Study at Beauty Care and Anti-Aging Clinic Service in Surabaya - Ervina Fernandes; Hatane Semuel; Michael Adiwijaya (Master of Management, School of Business and Management, Petra Christian University, 2020)
This study examines whether online advertising on social media Instagram influences purchase intention through shopping motivation. The study uses causal quantitative research methods with 110 respondents using purposive sampling techniques. The results show that Instagram social media online advertising has a positive effect on buying interest and utilitarian and hedonic shopping motivations for beauty care products and services. Hedonic motivation influences the customer's desire to buy beauty care products and services, but conversely, utilitarian motivation does not affect the interest in buying beauty care products and services. Online advertising can affect utilitarian shopping motivation but does not affect buying interest, while online advertising affects hedonic motivation and then affects customers in buying beauty care at Favourite Beauty Care Surabaya.